The Role Of The Teacher in Implementing The Project To Strengthen The Profile Of Pancasila Students : Peran Guru Dalam Pelaksanaan Proyek Penguatan Profil Pelajar Pancasila - Ningsih, Helsa Mariana; Achadi, Wasith (Thawalib: Jurnal Kependidikan Islam, 2024)
ABSTRACT The teachers are not only responsible for delivering religious materials, but also for instilling moral and ethical values relevant to democracy in the context of Pancasila. The method used is qualitative with a case study approach. The data collection techniques consisted of observation, interviews, and documentation. The results showed that teachers play an active role as planners, facilitators, assistants, supervisors, and consultants in Project for Strengthening Pancasila Student Profiles activities. Not only that, teachers always collaborate with other teachers to design learning modules, assist students in projects, and supervise the implementation of activities. Teachers endeavour to integrate Pancasila and Islamic values in learning, encouraging students to think critically and creatively. This research emphasises the importance of character education in the new curriculum which aims to shape students into individuals who are faithful, pious, independent, and have a good understanding of democracy and human rights.